DIAGNOSTIC POSSIBILITIES OF PROJECTIVE METHODS IN THE STUDY OF PERSONALITY (Scientific journal of the Fergana State University, 2023)
This article describes the diagnostic possibilities, advantages and disadvantages of projective methods in the study of personality. The procedures for conducting one of the projective methods are also analyzed, which help to determine the characteristics and interests of a person